Successful Surgical Management of Haemodynamically Evaluated Uterine Torsion in a Bitch - Bhathra, N R; Gupta, Chhavi; V, Prabaharan; A, Ganesan; A, Sabarinathan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Uterine torsion is defined as the twisting of the uterus or uterine horn perpendicular to its long axis and is more commonly observed in multiparous animals (Thilagar et al., 2011). Predisposing factors for uterine torsion are excessive fetal movements, lack of fetal fluids, premature uterine contractions, usage of ecbolic therapy, hereditary weakness of uterine ligament, hyperactivity of the pregnant animal like jumping, rolling, running in late gestation period etc (Gupta et al., 2020). The clinical signs and haemodynamic changes of the middle uterine artery are directly proportional to the torsion degree, which can vary between 180° and 90° both clockwise and counter clockwise, hence, these parameters are considered as prognostic indicators (Thilagar et al., 2011). Doppler ultrasound evaluation of uterine blood flow is a non-invasive technique for early diagnosis of uterine torsion in canines. Further, velocimetric indices could be useful to differentiate the side of torsion (Sudha et al., 2019). This document represents successful surgical management of haemodynamically evaluated uterine torsion in a bitch.